From west to east, working as a woman in foreign service - Åkerblom, Ida (2022)
This master's thesis attempts to answer the research question "What challenges do Western women working in foreign service in majority-Muslim countries perceive and confront?". This is completed by sampling a group of women via five semi-structured interviews originating from Sweden, Finland, and Czech Republic and have been stationed in Iran, Egypt, Pakistan, and Algeria. The interviews are further discussed, analyzed and similarities with previous literature and theoretical framework are drawn, from where recommendations are made.